RELN Mutations in Autism Spectrum Disorder - Lammert, Dawn B.; Howell, Brian W. (Frontiers in Cellular Neuroscience, 2016)
RELN encodes a large, secreted glycoprotein integral to proper neuronal positioning during development and regulation of synaptic function postnatally. Rare, homozygous, null mutations lead to lissencephaly with cerebellar hypoplasia, accompanied by developmental delay and epilepsy. Until recently, little was known about the frequency or consequences of heterozygous mutations. Several lines of evidence from multiple studies now implicate heterozygous mutations in RELN in autism spectrum disorders (ASD). RELN maps to the AUTS1 locus on 7q22, and at this time over 40 distinct mutations have been identified that would alter the protein sequence, four of which are de novo. The RELN mutations that are most clearly consequential are those that are predicted to inactivate the signaling function of the encoded protein, and those that fall in a highly conserved RXR motif found at the core of the 16 Reelin subrepeats. Despite the growing evidence of RELN dysfunction in ASD, it appears that these mutations in isolation are insufficient and that secondary genetic or environmental factors are likely required for a diagnosis.